Correction to: Supplementation of Zinc Palm Oil Soap Improves Feed Fermentability and Unsaturated Fatty Acid Profile in Rumen Liquid - Muktiani, A.; Widiyanto, W.; Pandupuspitasari, N. S. (Tropical Animal Science Journal, 2025)
Correction to: Tropical Animal Science Journal, 47(3), 371-380. https://doi.org/10.5398/tasj.2024.47.3.371 An error occurred on Page 373, Table 1, on “Note” under the table. The previous version was written: 1Total digestible nutrients (TDN) were calculated using TDN (%DM). TDN = -17.2649 + 1.2120(PK) + 0.8352(BETN) + 2.4637(LK) + 0.4475(SK), according to Wardeh (1981). The correct version should be: 1Total digestible nutrients (TDN) were calculated using TDN (%DM). TDN = -17.2649 + 1.2120(CP) + 0.8352(NFE) + 2.4637(EE) + 0.4475(CF), according to Wardeh (1981).